Heredity of coat colour variation in the African Buffalo (Syncerus caffer) - (:unkn) unknown (My University, 1980)
The « savana » subspecies of the African Buffalo (Syncerus Caffer caffer) is black the « forest» subspecies (Syncerus caffer manus) is red with black extremities. The F1 which were obtained at the Museum d’Histoire Naturelle of Paris were intermediary, red but with a greater extension of the black areas. One can think than the two subspecies differ from one another in one allele at the locus Agouti A : caffer could probably be aa, nünus carrying the Ay allele for the red with black extremities. The formula of both at the E locus could be the same : E+E+
Keywords: African Research